Substitution of Commercial Feed with Fermentation of Coffee Skins Using Local Micro-Organisms for the Reproduction Rate of Landrace Pigs - I Dewa Nyoman Sudita; I Gusti Agus Maha Putra Sanjaya; Stefanus Nahak (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2023)
The development of pig livestock is supported by feed that has a high nutritional content, namely fermented coffee skin which can increase livestock reproduction to increase livestock production and productivity. The aim of the study was to evaluate the substitution of fermented coffee skins on the reproduction of landrace sows and at what level the substitution of fermented coffee skins affected the reproduction of landrace pig. This research method used a completely randomized design (CRD) with four treatments T0 = 100% Commercial Feed, T1 = Commercial Feed (95%) + 5% Fermented Coffee skin, T2 = Commercial Feed (90%) + 10% Fermented Coffee skin, T3 = Commercial feed (85%) + 15% fermented coffee skin. Each treatment was repeated 3 times so that there were 12 experimental livestock units. The results showed that substitution of fermented coffee skin had no significant effect on estrus, namely 2.67-3.00 days, estrus cycle 19.67-20.67 days, birth weight 1.32-1.65 kg, and mortality 0.33-1.67%, but 5% fermented coffee skin substitution had a significant effect on gestational age, namely 113.67 days, litter size of 11 tails, weaning weight of 8.05 kg. It can be concluded that 5% fermented coffee skin substitution gave the best results on estrous variables, estrus cycle, litter size, birth weight, weaning weight and mortality. Keywords: Coffee Skin, Fermentation, Pig, Reproduction